Exploring consumers’ perceptions of eco-conscious apparel acquisition behaviors - Hiller Connell, Kim Y. (My University, 2011)
Purpose – The purpose of this research is to advance understanding of the socially responsible apparel consumer by exploring apparel consumption behaviors perceived by consumers to be eco-conscious. Design/methodology/approach – This study used a qualitative approach to collect and analyze data from 26 American apparel consumers. Data collection for the study occurred through semi-structured interviews. Findings – Results indicate that the participants engaged in a number of perceived eco-conscious apparel acquisition behaviors. First, they adhered to acquisition limits by acquiring apparel based on need and extending the lifetime of their apparel. Second, they acquired apparel made from fibers or having other attributes perceived as environmentally preferable. Finally, they acquired apparel through sources believed to be environmentally preferable, including second-hand sources, eco-conscious companies, independently owned companies, and home sewing. Research limitations/implications – The sample of 26 American consumers means that the results cannot be widely generalized. Future research should examine the apparel acquisition behaviors of a larger sample and include consumers from outside the USA. Practical implications – This study provides evidence that consumers engage in a range of eco-conscious apparel acquisition behaviors, and a market segment of eco-conscious apparel consumers exists. Apparel industry professionals can use this baseline information to aid in the development of eco-conscious apparel consumption strategies. Originality/value – This study contributes to increased understanding of eco-conscious apparel consumption, an area with limited previous research, by identifying apparel acquisition behaviors that consumers perceive to be eco-conscious. The findings are valuable in the promotion of eco-conscious apparel consumption.
Keywords: Garment industry; Consumer behavior; Decision making; Social responsibility